Efficacy and safety of acupuncture treatment for fatigue after COVID-19 infection: study protocol for a pilot randomized sham-controlled trial - Kim, Sung-A.; Lee, Ji-Su; Kim, Taegon; Kim, Tae-Hun; Kwon, Sunoh; Kang, Jung Won (Frontiers in Neurology, 2023)
Background As the coronavirus disease 2019 (COVID-19) pandemic has spread globally, its sequelae, called Long COVID, have persisted, troubling patients worldwide. Although fatigue is known to be the most frequent among Long COVID symptoms, its mechanism and treatment have not been clearly demonstrated. In 2022, we conducted a preliminary prospective case series and found that acupuncture and moxibustion were feasible interventions for fatigue. This study is a pilot patient-assessor-blinded randomized sham-controlled trial to evaluate the efficacy and safety of acupuncture treatment for patients with fatigue that has persisted for at least 4 weeks after recovery from COVID-19. Methods Thirty patients will be recruited and randomly assigned to either the acupuncture or sham acupuncture treatment groups. Treatment will be conducted thrice a week for both groups during 4 weeks. The primary outcome will be the efficacy and safety of acupuncture, including numeric rating scale (NRS), brief fatigue inventory (BFI), fatigue severity scale (FSS), and adverse event evaluation. Secondary outcomes will be evaluation of improvement in the comorbid symptoms of fatigue and feasibility variables. Outcome variables will be assessed before treatment, 4 weeks after treatment, and 8 weeks after treatment completion. Discussion The results of this study will be used to clarify the efficacy and safety of acupuncture treatment for persistent fatigue in patients with Long COVID. Additionally, the feasibility of the study design was validated to provide evidence for future full-scale randomized controlled trials. Clinical trial registration: identifier: KCT0008656 https://cris.nih.go.kr/cris/search/detailSearch.do?seq=24785&search_page=L.